STRATEGI PEMNGEMBANGAN PARIWISATA SEJARAH DI KABUPATEN ROKAN HULU (STUDI PADA OBJEK WISATA MAKAM RAJA-RAJA RAMBAH) - Sahdin Hasibuan; Hasim As'ari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Tourism is a new type of industry that is able to generate rapid economic growth in the provision of jobs. RokanHulu Regency is one of the regencies in Riau Province which has a lot of variety of tourism such as nature tourism and historical tourism. One of them is the historical tourist attraction of the Tomb of the Kings of Rambah in RambahHilir District. This tour is a tourism that has great potential if it is developed, but unfortunately the development of historical tourism is still not maximized so that it is less attractive to tourists. Therefore, a suitable strategy is needed in the development of historical tourism objects, the Tomb of the Kings of Rambah. The theory used in this research is the theory of adaptive strategy from Miles and Snow to determine the right strategy in overcoming the problem. This study uses a qualitative descriptive method with triangulation techniques, data collection by interview, observation, and documentation. The results of this study are the implementation of development strategies on historical tourism of the Tomb of the Kings of Rambah has been carried out but is not optimal, therefore an adaptive strategy is carried out, namely the selection of technology, determining the authority for coordination, embodiment, system regulation and inhibiting factors in the implementation of the strategy for developing historical tourism objects, the Tomb of the Kings of Rambah, among others: funding, skilled human resources, and regulation. In order for tourism to be directed and able to compete with other regions, there will be many investors who are willing to cooperate with the government of RokanHulu Regency. Keywords: Strategy, Development, Tourist Object